Efficient Authentication Scheme Using PCCP - Ameen, J. Noorul; Mohamed, J. Jamal; Begam, N. Nilofer (COMPUSOFT: An International Journal of Advanced Computer Technology, 2024)
There is an increasing need to design and deploy multi featured networking applications due to the fast growth of the Internet infrastructure and the use of large-scale complex applications. This paper presents an integrated evaluation of the Persuasive Cued Click-Points graphical password scheme, including usability and security evaluations, and implementation considerations. An important usability goal for knowledge-based authentication systems is to support users in selecting passwords of higher security, in the sense of being from an expanded effective security space. We use persuasion to influence user choice in click -based graphical passwords, encouraging users to select more random, and hence more difficult to guess, click-points.